Microdiversification in genome-streamlined ubiquitous freshwater Actinobacteria - Neuenschwander, Stefan M; Ghai, Rohit; Pernthaler, Jakob; Salcher, Michaela M (The ISME journal, 2018)
Actinobacteria of the acI lineage are the most abundant microbes in freshwater systems, but there are so far no pure living cultures of these organisms, possibly because of metabolic dependencies on other microbes. This, in turn, has hampered an in-depth assessment of the genomic basis for their success in the environment. Here we present genomes from 16 axenic cultures of acI Actinobacteria. The isolates were not only of minute cell size, but also among the most streamlined free-living microbes, with extremely small genome sizes (1.2-1.4 Mbp) and low genomic GC content. Genome reduction in these bacteria might have led to auxotrophy for various vitamins, amino acids and reduced sulphur sources, thus creating dependencies to co-occurring organisms (the 'Black Queen' hypothesis). Genome analyses, moreover, revealed a surprising degree of inter- and intraspecific diversity in metabolic pathways, especially of carbohydrate transport and metabolism, and mainly encoded in genomic islands. The striking genotype microdiversification of acI Actinobacteria might explain their global success in highly dynamic freshwater environments with complex seasonal patterns of allochthonous and autochthonous carbon sources. We propose a new order within Actinobacteria ('Candidatus Nanopelagicales') with two new genera ('Candidatus Nanopelagicus' and 'Candidatus Planktophila') and nine new species.
Keywords: zastoupení bazí; Biodiversity; Phylogeny; Genome, Bacterial; biodiverzita; genom bakteriální; DNA, Bacterial; DNA bakterií; Actinobacteria; sladká voda; Fresh Water; Metabolic Networks and Pathways; fylogeneze; Base Composition; metabolické sítě a dráhy